2021
DOI: 10.1021/acsenergylett.1c00342
|View full text |Cite
|
Sign up to set email alerts
|

Localized Electron Density Engineering for Stabilized B-γ CsSnI3-Based Perovskite Solar Cells with Efficiencies >10%

Abstract: Black orthorhombic (B-γ) CsSnI3 with low toxicity and excellent optoelectronic properties is a promising candidate for perovskite solar cell (PSC). However, the performance of the B-γ CsSnI3-based PSCs is much lower than their lead-based or organotin-based counterparts due to the heavy self-doping of Sn2+ to form Sn4+ under ambient-air conditions. Here, this undesirable oxidation in CsSnI3 is restricted by engineering the localized electron density with phthalimide (PTM) additive. The lone electron pairs of NH… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

8
159
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 169 publications
(176 citation statements)
references
References 48 publications
8
159
1
Order By: Relevance
“…14 Recently, Ye et al used localized electron density engineering to restrict undercoordinated Sn 2+ , resulting in reduced defect density and relatively grain-ordered CsSnI 3 films. 29 Herein, we combine the aforementioned two principal issues, proposing the two-step temperature annealing and surface cationic coordination dual treatment strategy (DTS) to achieve high-performance CsSnI 3 PSCs. The first annealing step at a low temperature of 40 °C for 5 min slows down the crystal growth of CsSnI 3 films and produces many small crystal grains.…”
Section: Introductionmentioning
confidence: 99%
“…14 Recently, Ye et al used localized electron density engineering to restrict undercoordinated Sn 2+ , resulting in reduced defect density and relatively grain-ordered CsSnI 3 films. 29 Herein, we combine the aforementioned two principal issues, proposing the two-step temperature annealing and surface cationic coordination dual treatment strategy (DTS) to achieve high-performance CsSnI 3 PSCs. The first annealing step at a low temperature of 40 °C for 5 min slows down the crystal growth of CsSnI 3 films and produces many small crystal grains.…”
Section: Introductionmentioning
confidence: 99%
“…[7] Promisingly, Li et al have shown that CsSnI 3 perovskite inverted PV devices maintained >90% of their starting efficiency after 500 h light soaking when encapsulated with glass. [30] To understand the intrinsic stability of perovskite PVs with a Cu top electrode toward degradation in ambient air, which inevitably ingresses into the device even with encapsulation, it is useful to test the devices in ambient air under 1 sun constant illumination and under electrical load. Without device encapsulation such a test is clearly an accelerated degradation test, since for practical application PV devices would always be encapsulated and so the rate of air ingress into the device would be many orders of magnitude slower.…”
Section: Introductionmentioning
confidence: 99%
“…With record PCEs beyond 10.1%, 16–18 CsSnI 3 perovskite solar cells (PSCs) have shown an increasing competitive edge. 19–22 CsSnI 3 can hold two crystal phases at room temperature, namely, the corner-linked three-dimensional (3D) black orthorhombic phase (B-γ) perovskite and the edge-connected one-dimensional (1D) yellow phase (Y) one.…”
Section: Introductionmentioning
confidence: 99%
“…19–22 CsSnI 3 can hold two crystal phases at room temperature, namely, the corner-linked three-dimensional (3D) black orthorhombic phase (B-γ) perovskite and the edge-connected one-dimensional (1D) yellow phase (Y) one. 17 However, once exposed to air or organic solvents, B-γ-CsSnI 3 rapidly degrades to Y-CsSnI 3 , subsequently leading to severely attenuated PCEs under ambient conditions. 17,23 Compared to Y-CsSnI 3 , the superior photoelectric properties of B-γ-CsSnI 3 depends on the 3D corner-shared [SnI 6 ] 4− octahedral structure, which benefits the transport of photo-induced carriers along …Sn–I–Sn–I–Sn… chains.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation